Early immunotherapy in a patient with myelin oligodendrocyte glycoprotein antibody-associated disease with syphilis and acquired immunodeficiency syndrome: a case report - Zhang, Qiu-Xia; Zhang, Lin-Jie; Zhao, Bin (Frontiers in Immunology, 2025)
This is the case of a 41-year-old man who presented with blurred vision, unconsciousness, and fever with a positive Babinski sign on both sides. Blurred vision, unconsciousness, and fever are commonly seen in neurology and emergency settings, with a wide range of potential etiologies. Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) often occurs after infection, but cases of syphilis and human immunodeficiency virus as precursors are rarely reported. We report a case of MOGAD with syphilis and acquired immunodeficiency syndrome. Additionally, the study summarizes the disease’s clinical manifestations, therapy, prognosis, and outcome and highlights the importance of timely and accurate immune regulation therapy.